1968
DOI: 10.1111/j.1476-5381.1968.tb00480.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CHLORPROMAZINE ON 14C‐GLUCOSE METABOLISM IN MOUSE LIVER AND BRAIN

Abstract: Chlorpromazine in high concentrations decreases energy production in tissues in vitro by inhibiting cellular respiration and phosphorylation (Quastel, 1965). Berger (1957) found uncoupling of phosphorylation in liver, but not in brain mitochondria exposed to chlorpromazine. The precise site of uncoupling of the respiratory enzyme chain in the liver has been identified by Dawkins, Judah & Rees (1959), who also observed similar effects in the brain in the presence of 2 x 10-'M chlorpromazine. Chance (1959) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The neuroleptic drugs chlorpromazine and promethazine (C+P), both derivatives of the drug phenothiazine, have been used for their anti-psychotic and sedative effects since the 1950s 5 , 6 . Often administered in combination 6 9 , C+P appear to exert their effects on the nervous system through the inhibition of carbohydrate oxidation 8 , 10 ; several studies have reported beneficial antioxidant effects achieved with these agents 7 , 9 , 11 , 12 . Additionally, recent unpublished data from our group have demonstrated that phenothiazines applied after stroke suppress brain metabolism and decrease peroxide production.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroleptic drugs chlorpromazine and promethazine (C+P), both derivatives of the drug phenothiazine, have been used for their anti-psychotic and sedative effects since the 1950s 5 , 6 . Often administered in combination 6 9 , C+P appear to exert their effects on the nervous system through the inhibition of carbohydrate oxidation 8 , 10 ; several studies have reported beneficial antioxidant effects achieved with these agents 7 , 9 , 11 , 12 . Additionally, recent unpublished data from our group have demonstrated that phenothiazines applied after stroke suppress brain metabolism and decrease peroxide production.…”
Section: Introductionmentioning
confidence: 99%